An Elastic Autonomous Self‐Healing Capacitive Sensor Based on a Dynamic Dual Crosslinked Chemical System. Issue 33 (5th July 2018) - Zhang, Qiuhong; Niu, Simiao; Wang, Li; Lopez, Jeffrey; Chen, Shucheng; Cai, Yifeng; Du, Ruichun; Liu, Yuxin; Lai, Jian‐Cheng; Liu, Ling; Li, Cheng‐Hui; Yan, Xuzhou; et al.
Abstract: Adopting self‐healing, robust, and stretchable materials is a promising method to enable next‐generation wearable electronic devices, touch screens, and soft robotics. Both elasticity and self‐healing are important qualities for substrate materials as they comprise the majority of device components. However, most autonomous self‐healing materials reported to date have poor elastic properties, i.e., they possess only modest mechanical strength and recoverability. Here, a substrate material designed is reported based on a combination of dynamic metal‐coordinated bonds (β‐diketone–europium interaction) and hydrogen bonds together in a multiphase separated network. Importantly, this material is able to undergo self‐healing and exhibits excellent elasticity. The polymer network forms a microphase‐separated structure and exhibits a high stress at break (≈1.8 MPa) and high fracture strain (≈900%). Additionally, it is observed that the substrate can achieve up to 98% self‐healing efficiency after 48 h at 25 °C, without the need of any external stimuli. A stretchable and self‐healable dielectric layer is fabricated with a dual‐dynamic bonding polymer system and self‐healable conductive layers are created using polymer as a matrix for a silver composite. These materials are employed to prepare capacitive sensors to demonstrate a stretchable and self‐healable touch pad. Abstract : Dynamic metal‐coordinated bonds (β‐diketone–europium interaction) and hydrogen bonds, are combined in a multiphase separated network, in a new strategy to enable a robust and elastic capacitive sensor with autonomous self‐healing properties.